2007
DOI: 10.1590/s0037-86822007000300011
|View full text |Cite
|
Sign up to set email alerts
|

Doença meningocócica: comparação entre formas clínicas

Abstract: A doença meningocócica (DM) persiste em todo o mundo sob formas de surtos, epidemias ou casos esporádicos, apresentando considerável letalidade e seqüelas 22 26 . Formas clínicas clássicas são agrupadas como meningite e/ou meningoencefalite sem e com septicemia, e como septicemia sem acometimento do sistema nervoso central. Meningite e septicemia são acometimentos muito diferentes, com fisiopatogenia, tratamentos e desfechos distintos 29 32 34 . E, a própria septicemia apresenta letalidade variável, entre 20 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
9

Year Published

2011
2011
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
0
1
0
9
Order By: Relevance
“…Other factors may be associated with more severe cases of the disease: for example, a study related to poor perfusion of cerebral capillaries due to the accession of N. meningitides, [24] and other related cortisol levels in the CSF (which in turn is related to the serum level) with the severity of bacterial meningitis. [25] Stella-Silva et al, [26] Also with regard to laboratory tests, study in Portugal found an average of 22,042/mm 3 white blood cell in 110 pediatric patients with bacterial meningitis (67% meningococcal meningitis, a percentage that differs from the Brazilian studies cited here) and an average of 2104 leukocytes/mm³ in CSF. The study also compared these values in patients with viral meningitis, finding an average of 13,233 blood leukocyte and 277 leukocytes / mm³ in CSF.…”
Section: Discussionmentioning
confidence: 58%
“…Other factors may be associated with more severe cases of the disease: for example, a study related to poor perfusion of cerebral capillaries due to the accession of N. meningitides, [24] and other related cortisol levels in the CSF (which in turn is related to the serum level) with the severity of bacterial meningitis. [25] Stella-Silva et al, [26] Also with regard to laboratory tests, study in Portugal found an average of 22,042/mm 3 white blood cell in 110 pediatric patients with bacterial meningitis (67% meningococcal meningitis, a percentage that differs from the Brazilian studies cited here) and an average of 2104 leukocytes/mm³ in CSF. The study also compared these values in patients with viral meningitis, finding an average of 13,233 blood leukocyte and 277 leukocytes / mm³ in CSF.…”
Section: Discussionmentioning
confidence: 58%
“…As epidemias geralmente surgem em intervalos de tempo irregulares e com magnitudes diversas (Santos, 2005;Puriccelli, 2004;Stella-Silva, 2007;Stephens, 2007 (Stephens, 2007;Caugant, 2007). A partir de então, pode se manifestar de diversas formas no indivíduo (Santos, 2005;Duarte, 2005;Stella-Silva, 2007). A ausência de anticorpos bactericidas é o fator individual mais importante no desenvolvimento da doença meningocócica (Stephens, 2007).…”
Section: Custos Do Programa De Vacinaçãounclassified
“…Dados do Estado de São Paulo evidenciam diminuição na incidência de casos do sorogrupo B e manutenção da incidência de casos do sorogrupo C, o que fez com que a proporção de C ultrapassasse a de B (Carvalhana, 2004 (Stephens, 2007;Stella-Silva, 2007). Silva, 2007;Stephens, 2007).…”
Section: Figuraunclassified
See 2 more Smart Citations